DRIED APRICOT BRANDY: DEVELOPMENT AND PHYSICAL-CHEMICAL CHARACTERIZATION OF A NEW DRINK - Leite, Marcelo Teixeira; Pontes, Débora Telma de Souza (Seven Editora, 2025)
The global distilled spirits market has been influenced by a notable change in consumer behavior, with consumers increasingly looking for products with a different flavor profile. In this context, fruit brandies have become an interesting option due to the variety of flavors they can offer. The aim of this work was to produce a fruit brandy using dried apricots as the raw material. Dried apricots have an intense and unique flavor, which is in line with new consumer trends. To produce this drink, a fermentation must was initially prepared, consisting of water from macerating the dried fruit. The must was inoculated with a commercial strain of Saccharomyces cerevisiae and fermentation was carried out in a single batch system in a closed vessel equipped with an airlock. Distillation was carried out in a copper alembic equipped with a deflegmator and the head, heart and tail fractions were separated according to the estimated volume of distillate. The brandy obtained was subjected to physical-chemical analysis using gas chromatography with a flame ionization detector. The results showed that all the analytical parameters complied with Brazilian legislation. In terms of sensory characteristics, the drink was clear, with a soft, fruity smell and taste. DOI: https://doi.org/10.56238/sevened2025.021-021